Total versus partial knee replacement in patients with medial compartment knee osteoarthritis: the TOPKAT RCT - Beard, DJ; Davies, LJ; Cook, JA; MacLennan, G; Price, A; Kent, S; Hudson, J; Carr, A; Leal, J; Campbell, H; Fitzpatrick, R; Arden, N; et al. (NIHR Journals Library, 2020)
Background Late-stage medial compartment knee osteoarthritis can be treated using total knee replacement or partial (unicompartmental) knee replacement. There is high variation in treatment choice and insufficient evidence to guide selection.